Vốn xã hội, chuyển đổi số và đổi mới mô hình kinh doanh của các doanh nghiệp tại khu vực Đông Nam Bộ, Việt Nam - Trần Nha , Ghi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Based on social network, social capital theory, and resource-based theory, the study explained digital transformation and business model innovation of firms during the COVID-19 pandemic. The study examined the relationship between social capital, digital transformation and business model innovation, and the mediating role of digital transformation. Partial Least Squares Structural Modeling (PLS-SEM) was performed with a sample size of 218 managers. The research results show that there are positive and statistically significant relationships between social capital, digital transformation, and business model innovation. The study explored the partial meditation role of digital transformation between social capital and business model innovation. In addition, the study also proposed managerial implications to managers in actively building relationship networks with stakeholders such as government agencies and business partners (customers, competitors, and suppliers of digital platform services). Finally, the study suggested some limitations and directions for further research.